Kala-azar victims in Bangladesh: their socio-cultural background and environmental surroundings - Karim, A.H.M Zehadul (Serials Publications, 2012)
Kala-azar1 or viscereal leishmaniasis is a major vector-borne disease infected by parasites of the genus leishmania, which is transmitted to human body through bite of a female phlebotomine sandfly. It is scatteredly prevalent in many parts of the world; but most frequently it has been occurring in parts of Bangladesh, India, Nepal, Brazil and Sudan.2 Kala-azar has always been treated as a very severe disease since past, and in the Indian sub-continent, it was first detected in the Bengal belt of Burdwan in India. Then it was found occuring epidemically and endemically in different areas of Assam, Bihar, West Bengal, the eastern districts of Uttar Pradesh, foothills of Sikkim and to a lesser extent in Tamil Nadu and Orissa (Epidemology of Communicable Diseases n.d.). It is suspected that kala-azar fever thus entered in many parts of Bangladesh across the border belt of India. As a consequence during early 1960s, a regular insecticide spraying for malaria eradication was started under the leadership of Malaria Eradication Program (MEP). The program was running very successfully with the assistance and economic support from WHO, USAID and DANIDA. The activities of the MEP later on slowly squeezed and after the liberation, and by the year 1977, it was totally abolished and was absorbed and merged with General Health Services of the Ministry of Health. As a result and since then, vector control in the name of malaria eradication practically disappeared from Bangladesh (Mondal et.al. 2008). In recent years, Kala-azar has become an acute public health problem in many areas of Bangladesh. It is reported to us from multifarious sources that there has had occurred quite a large number of Kala-azar incidences in few areas of Bangladesh (see Banglapedia 2004). The situation seems to be alarming as it was learned that there had been a few death cases in Mymenshing and Rajshahi regions. For that reason, we on behalf of ICDDR,B have conducted a research under in collaboration with the Tropical Disease Research (TDR), WHO, Geneva to improve kala-azar case detection and case management as well as kala-azar vector control in Bangladesh. This paper depended partially on those data collected for the larger project, 3 but as an anthropologist, I have dealt with the victims more intensively by my own observation and further investigation from empirical point of view to know the socio-cultural and environmental reasons for kala-azor fever.